Prognostic value of 18F-fluorodeoxyglucose positron emission tomography in patients with gastric neuroendocrine carcinoma and mixed adenoneuroendocrine carcinoma - Lim, Sun Min; Kim, Hyunki; Kang, Beodeul; Kim, Hyo Song; Rha, Sun Young; Noh, Sung Hoon; Hyung, Woo Jin; Cheong, Jae-Ho; Kim, Hyoung-Il; Chung, Hyun Cheol; Yun, Mijin; Cho, Arthur; et al. (Annals of nuclear medicine, 2016)
Objective Gastric neuroendocrine carcinomas (NEC) and mixed adenoneuroendocrine carcinoma (MANEC) are very rare, aggressive tumors of the stomach. We aimed to examine predictive role of pretreatment 18 F-FDG PET/CT-assessed metabolic parameter of primary tumors and metastases in patients with gastric NEC and MANEC. Methods We conducted a review of the 27 patients with histopathologically confirmed NECs ( n = 10) and MANEC ( n = 17) of the stomach at our institution between January 2005 and December 2012. All patients underwent 18 F-FDG-PET examination at diagnosis. Metabolic parameters [SUV max , SUV mean , metabolic tumor volume (MTV) and total lesion glycolysis (TLG)] of the primary tumor and metastases on baseline PET/CT were analyzed. Results The median follow-up duration was 39.4 months (95 % CI 20.0–58.1 months) and the median overall survival (OS) was 25.7 months (95 % CI 14.1–37.2 months). All gastric lesions were well visualized (average SUV max = 12.0, range 3.0–41.8). When subjects were divided into two groups by ROC cut-off value of 210.9 and 612, patients with high TLG in primary lesion and metastases showed poorer prognosis compared to low TLG patients ( P = 0.09, P = 0.002, respectively). In the sub-analysis of patients with metastasis ( n = 12), patients with high TLG in whole body tumor showed significantly shorter OS compared to those with low TLG (31.7 ± 11.4 vs. 7.2 ± 2.1 months, P = 0.006). Conclusion 18 F-FDG PET/CT is useful in evaluating prognosis of advanced gastric cancer with neuroendocrine carcinoma components. Baseline MTV of primary gastric cancer with metastatic disease, and MTV, TLG of metastases may be prognostic markers in patients with gastric NEC and MANEC.